(untitled) (Scientific journal of the Fergana State University, 2023)
The credit-module system is the future of education. The purpose of this article is to discuss the conditions for establishing the credit-module system in higher education institutions, to show the advantages of this system, to analyze the trends of the origin of the system and to make suggestions.